Lattice swelling and modulus change in a helium-implanted tungsten alloy: X-ray micro-diffraction, surface acoustic wave measurements, and multiscale modelling. (1st May 2015) - Hofmann, F.; Nguyen-Manh, D.; Gilbert, M.R.; Beck, C.E.; Eliason, J.K.; Maznev, A.A.; Liu, W.; Armstrong, D.E.J.; Nelson, K.A.; Dudarev, S.L.
Abstract: Using X-ray micro-diffraction and surface acoustic wave spectroscopy, we measure lattice swelling and elastic modulus changes in a W-1% Re alloy after implantation with 3110 appm of helium. An observed lattice expansion of a fraction of a per cent gives rise to an order of magnitude larger reduction in the surface acoustic wave velocity. A multiscale model, combining elasticity and density functional theory, is applied to the interpretation of observations. The measured lattice swelling is consistent with the relaxation volume of self-interstitial and helium-filled vacancy defects that dominate the helium-implanted material microstructure. Larger scale atomistic simulations using an empirical potential confirm the findings of the elasticity and density functional theory model for swelling. The reduction of surface acoustic wave velocity predicted by density functional theory calculations agrees remarkably well with experimental observations.